(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the different views of linguists about the linguistic nature of the epithet, which is a figure of speech. The use of the epithet as a speech phenomenon at the level of the language structure, in high abstraction, consists first of all in studying its linguistic aspects. In such an approach to the study of epithet, the first task is to separate it from other stylistic tools and determine its place in the system of other expressive tools available in our language. In order to analyze the linguistic features of the epithet, the study refers to scientific research works of linguists, dictionaries and textbooks, examples of Uzbek literature of the 20th century. The analysis of the found examples helps to gain a deeper understanding of how epithet compounds occur in speech, their theory, and their impact on cognitive processing.